Nota sobre deficiÃªncia e toxidez de boro em espÃ©cies cultivadas do gÃªnero ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ - Malavolta, E.; Trani, P. E.; Athayde, M. F.; Braga, N. R.; Nogueira, S. S. S.; Moraes, S. A. (REVISTA DE AGRICULTURA, 2020)
Nota sobre deficiÃªncia e toxidez de boro em espÃ©cies cultivadas do gÃªnero ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´